Gambling minds: what lies behind the BETS? - César Augusto Trinta Weber; Antonio Geraldo da Silva (Debates em Psiquiatria)
Online sports betting, known as bets, has gained exponential popularity, posing significant public health challenges. This article explores the neurobiological, psychological, and social factors underpinning gambling behavior, emphasizing the role of dopamine, intermittent reinforcement, and digital marketing. Gambling disorder, classified by the WHO as a mental health condition, is linked to rising cases of behavioral addiction. The discussion underscores the need for stricter regulation of betting platforms, protection of vulnerable populations, and strategies for prevention, diagnosis, and treatment, highlighting the urgency of public policies to address the social and emotional consequences of this practice.